Biomass and Carbon Stock in Ber (Ziziphus mauritiana Lam.) based Traditional Agroforestry System - Kumar, Deepak; Oraon, Prabhat Ranjan; Singh, Bijay Kumar; Kumar, Abhay; Toppo, Anupama (Indian Journal of Agroforestry, 2022)
Ziziphus mauritiana locally called as “ber” is a multipurpose tree which are grown naturally on the farm lands in Gumla district of Jharkhand. The study was conducted to estimate biomass and carbon stock in the farmer’s field, where Ziziphus mauritiana was intercropped with Vigna mungo (Black gram). The total average biomass of tree was 91.74 ± 8.31 t ha–1 whereas bole, branch, leaf and root contributed by 30.23%, 55.65%, 2.72%, and 11.35% respectively. The total average carbon stock was 40.28 ± 3.66 t ha–1, where in the percent of carbon stock of bole, branch, leaf and root were 57.89%, 29.96%, 9.23%, and 2.87% of the total carbon stock respectively. Biomass of agricultural crop was found 2.33 ± 0.07 t ha–1 whereas total average carbon stock was 1.97 ± 0.12 t ha–1. The contribution of crop residue biomass and grain yield percent to the total crop biomass was 80.25% and 21.03 % respectively and whereas carbon stock in crop residue and crop grain yield was found to be 92.89% and 7.11% in respectively. In agroforestry systems the mixed trees considered to be more efficient than sole stands in carbon sequestration.